Pengembangan Sistem Informasi Berbasis Website untuk Manajemen Perjalanan Dinas dengan Metodologi System Development Life Cycle (SDLC) pada PT Mahanusa Hijau Selaras - Selly Septiani; Joko Yuwono; Agun Bastiar Permana (Jurnal Teknik Informatika dan Teknologi Informasi, 2025)
PT Mahanusa Hijau Selaras is a consulting company that handles official business trip administration. The current process is still carried out manually using Microsoft Excel, including the submission of Travel Orders (SPD) and Travel Reports (LPD). This results in the accumulation of physical documents that need to be stored and risks causing delays, data duplication, and lack of real-time information transparency. This study aims to develop a web-based information system that simplifies the management process of business trip data, from submission, verification, to reporting, digitally and integrated. The methodology used is the System Development Life Cycle (SDLC) with a waterfall model approach, which includes stages of needs analysis, system design, implementation, and testing. This system is developed using PHP programming language with MySQL database. The results of the system development show improvements in efficiency, data accuracy, and ease of access to information for all parties involved. The system also significantly reduces the use of physical documents and simplifies the business trip administration process digitally and in real-time.